Critical and research evaluation of Gohar Khan Khattak Natia (Hymns) poetry in Qalb-ul-Aseer a book in Pashto language on the life of Holy Prophet (S.A.W) - Naeem, Abdul; Ayaz, Qabla (sourcecoder, 2022)
Gohar Khan Khan Khattak, the son of the famous Pashto warrior poet, Khushal Khan Khattak, got poetic genius from his father in legacy. He wrote a rate book in Pashto language on the life of the Holy Prophet (S.W.A), which is an ample evidence to prove him as rightful descendent of his father. The life of the Holy Prophet (S.W.A) is eulogized in prose, sprinkled with religious poetry (hymns). A manuscript of this unique book is available in Pashto Academy Peshawar University and in the Library of Peshawar Museum. The characteristics feature of this book is that the important events of the life of the Holy Prophet (S.A.W) have been adorned in elegant poetry alongside wonderful prose. The current research study critically evaluates Gohar Khan Khattak’s book (Qalb-ul-Aseer particularly the poetic part of it.